2020
DOI: 10.1073/pnas.1915719117
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria-derived metabolite, methylglyoxal, modulates the longevity of C. elegans through TORC2/SGK-1/DAF-16 signaling

Abstract: Gut microbes play diverse roles in modulating host fitness, including longevity; however, the molecular mechanisms underlying their mediation of longevity remain poorly understood. We performed genome-wide screens using 3,792 Escherichia coli mutants and identified 44 E. coli mutants that modulated Caenorhabditis elegans longevity. Three of these mutants modulated C. elegans longevity via the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 53 publications
(56 reference statements)
0
28
0
Order By: Relevance
“…mTOR, a relatively large (259 kDa) and highly conserved serine/threonine protein kinase regulated mainly by the PI3K/Akt signaling pathway [144], plays a central role in the aging process [121,122,145]. Research in the nematode C. elegans and the fruit fly Drosophila melanogaster was the first to show that mTOR regulates lifespan [146,147].…”
Section: Crosstalk Between Mtor and Nrf2mentioning
confidence: 99%
“…mTOR, a relatively large (259 kDa) and highly conserved serine/threonine protein kinase regulated mainly by the PI3K/Akt signaling pathway [144], plays a central role in the aging process [121,122,145]. Research in the nematode C. elegans and the fruit fly Drosophila melanogaster was the first to show that mTOR regulates lifespan [146,147].…”
Section: Crosstalk Between Mtor and Nrf2mentioning
confidence: 99%
“…Many longevity experiments have been performed using different rict ‐ 1 and sgk ‐ 1 alleles and RNAi under different conditions. What seems consistent, so far, is that in the presence of FUdR, deficient TORC2/SGK‐1 signalling shortens lifespan regardless of the food source when grown at 20°C, while at 25°C it shortens lifespan in OP50 but it extends lifespan in K12‐type bacterial strains (HT115 and BW25113; Alam et al, 2010; Chen et al, 2013; Mizunuma et al, 2014; Shin et al, 2020; Soukas et al, 2009; Xiao et al, 2013; Zhou et al, 2019). However, in the absence of FUdR, TORC2/SGK‐1 deficiency consistently extends lifespan regardless of food source and temperature (Evans et al, 2008; Gatsi et al, 2014; Hertweck et al, 2004; Mizunuma et al, 2014; Rahman et al, 2010; Shin et al, 2020; Soukas et al, 2009).…”
Section: Discussionmentioning
confidence: 73%
“…Thus, it is possible that additional mitochondrial stress could revert the ageing phenotype and other physiological responses of TORC2/SGK-1 animals, which already have compromised mitochondrial function (Aspernig et al, 2019;Gatsi et al, 2014;Zhou et al, 2019). In agreement, FUdR partially suppresses the extended lifespan of mitochondrial mutants (Shin et al, 2020). Thus, it is possible that mild mitochondrial dysfunction contributes to the extended lifespan of sgk-1 mutants.…”
Section: F I G U R Ementioning
confidence: 87%
“…Recently, it has been observed that physical exercise modulates gut microbiota in both humans and animals ( Clarke et al, 2014 ; Barton et al, 2018 ). Of note, bacteria-derived metabolites play critical roles in the modulation of aging and longevity in the host organism ( Smith et al, 2017 ; Shin et al, 2020 ). Thus, microbiota-derived metabolites could be important mediators of the benefits of exercise.…”
Section: Resultsmentioning
confidence: 99%